Progressive activation of CyclinB1-Cdk1 coordinates entry to mitosis - Gavet, Olivier (2010)
The CyclinB1-Cdk1 kinase is the catalytic activity at the heart of Mitosis Promoting Factor (MPF), yet fundamental questions concerning its role in mitosis remained unresolved. It is not known when and how rapidly CyclinB1-Cdk1 is activated in mammalian cells, nor how its activation coordinates the substantial changes in the cell at mitosis. Here, we have developed a FRET biosensor specific for CyclinB1-Cdk1 that enables us to assay its activity with very high temporal precision in living human cells. We show that CyclinB1-Cdk1 is inactive in G2 phase and activated at a set time before nuclear envelope breakdown, thereby initiating the events of prophase. CyclinB1-Cdk1 levels rise to their maximum extent over the course of approximately 30 min and we demonstrate that different levels of CyclinB1-Cdk1 kinase activity trigger different mitotic events, thus revealing how the remarkable reorganisation of the cell is coordinated at mitotic entry.